DHPAC, a novel synthetic microtubule destabilizing agent, possess high anti-tumor activity in vincristine-resistant oral epidermoid carcinoma in vitro and in vivo. (December 2017) - Zhang, Ying; Gong, Fu-Lian; Lu, Zhen-Ning; Wang, Hong-Yuan; Cheng, Yan-Na; Liu, Zhao-Peng; Yu, Lu-Gang; Zhang, Hui-Hui; Guo, Xiu-Li
Graphical abstract: Abstract: Multidrug resistance (MDR) is one of major obstacles to effective chemotherapeutic treatment of cancer. This study showed that DHPAC, 2-(6-ethoxy-3-(3-ethoxyphenylamino) −1-methyl-1, 4-dihydroindeno[1, 2-c]pyrazol-7-yloxy) acetamide, a novel compound that binds to the same site on microtubules as colchicine, has high anti-tumour activity in vincristine-resistant oral epidermoid carcinoma (KB/V) cells. It found that the presence of DHPAC strongly inhibited KB/V cell growth in vivo and in mice xenograft. The inhibitory effect of DHPAC is much stronger than that by colchicine in these KB/V cells (IC50 : 64.4 nM and 458.0 nM respectively). Treatment of the cells with DHPAC induced cell apoptosis by reducing mitochondrial membrane potential and altered the expression of several apoptosis-related proteins such as Bcl-2, Bax, Caspase-9, Cytochrome c and PARP. DHPAC treatment also caused cell rest in G2/M phase by regulating of the expression of a number of cell cycle-related proteins ( e.g. Cyclin B1, Cdc2, Cdc25b, Cdc25c, RSK2). Furthermore, DHPAC presence inhibits PTEN phosphorylation and PTEN/Akt/NF-κB signalling. Thus, DHPAC has potent anti-cancer activity in MDR tumuors and may be a potential therapeutic agent for the treatment of vincristine-resistant human oral epidermoid carcinoma.